Floral organ size control: Interplay between organ identity, developmental compartments and compensation mechanisms - Delgado-Benarroch, Luciana (Landes Bioscience, 2009)
Growth of lateral organs is a complex mechanism that starts with formation of lateral primordia.Basal developmental programs like polarity, organ identity and environmental cues influence the final organ size achieved via coordinated cell division and expansion. recent evidence shows that the precise balance between these two processes, known as compensation mechanisms, seems to be influenced by the identity of the organ. Furthermore, studies of mutants affected in floral organ size suggest the existence of developmental compartments within different floral whorls that show distinct compensation behaviors.